(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
Dictionary reviewing is an integral part of the lexicographic universe. However, lexicographers have called for generally applicable principles embracing both printed and electronic dictionaries. I propose that scholarly reviews contain information that is useful to their intended audiences and a set of principles that are generally applicable to achieve this goal. I suggest that reviewers may write useful reviews by treating the dictionary as an object of analysis and examination. I further propose that the lexicographic, factual and linguistic approaches should be combined with the three significant features of dictionaries: lexicographic functions, data and structures. Finally, I argue that a review should give a true and fair view of the dictionary, and this will strengthen the role of dictionary reviews in the scholarly discourse community.